ANALYSIS OF SMALL MARKETS LOCATED IN HISTORICAL NEIGHBORHOOD CENTERS LOCATED IN THE CITY OF SAMARKAND (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
Euphemisms are pivotal tools in political propaganda, especially in shaping narratives about war and peace. These linguistic expressions help obscure the true nature of controversial actions, reshaping public perceptions and swaying opinion on critical topics like military conflict. Politicians often use euphemisms to present violent actions as justified or noble, while portraying peace negotiations as weak or insufficient. This paper delves into the role euphemisms play in the discourse surrounding war and peace, assessing their influence on political rhetoric and public opinion. Through analysis of both historical and contemporary instances, the study reveals how euphemisms are employed to manage political narratives, influence public sentiment, and legitimize governmental decisions.